The development of interactive multimedia based lectora inspire on chemical bonding material for grade X senior high school - Sary, Putri Yustika; Iis Siti Jahro (ARKA INSTITUTE, 2022)
This research aims to determine to develop interactive multimedia based on the Lectora Inspire on chemical bonding for grade X Senior High School an, knowing the feasibility of developing interactive multimedia based on the Lectora Inspire on chemical bonding materials in accordance with the BSNP form assessment criteria. The type of research is (R&D) by implementing 4-D development model by Thiagarajan. The stages are define, design, develop, and disseminate. The results of media validation of the 3 validators showed that the product was included in the